Sensitivity difference of Streptococcus viridans on 35% Piper betle linn extract and 10% povidone iodine towards recurrent apthous stomatitis - Maharani Laillyza Apriasari; Bagus Soebadi; Hening Tuti Hendarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Oral ulceration often becomes the main reason for the patients to see a dentist. Therapy of the oral ulceration is by giving the palliative therapy with topical antiseptic. Nowadays, there are many researches concerning with the traditional medicines as alternative therapy. One of them is Piper betle linn which contains the antiseptic agent. Purpose: This research is aimed to observe the sensitivity difference of Streptococcus viridans on 35% Piper betle linn extract and 10%povidone iodine. Methods: This laboratory research was conducted by the post test only design with random complete design. The research sampel is Streptococcus viridans culture that was scrapped from the ulcer of the recurrent aphthous stomatitis patient, then it was replicated by using the Federer theory. Results: Inhibitory zone of 35% Piper betle linn extract is bigger than 10% povidone iodine. Conclusion: Streptococcus viridans are more sensitive to 35% Piper bittle linn extract than 10% povidone iodine. 35% Piper betle linn extract has more antibacterial effect than 10% povidone iodine.Latar belakang: Ulserasi rongga mulut seringkali menjadi alasan utama bagi pasien untuk memeriksakan diri ke dokter gigi. Terapi ulserasi rongga mulut adalah pemberian terapi paliatif kepada penderita, seperti: pemberian obat topikal yang mengandung antiseptik. Saat ini banyak penelitian dalam pengembangan obat tradisional yang dapat dijadikan sebagai obat alternatif. Salah satu diantaranya adalah daun sirih yang mengandung zat antiseptik. Tujuan: Penelitian ini bertujuan mengetahui perbedaan sensitivitas Streptococcus viridans terhadap ekstrak daun sirih 35% jika dibandingkan dengan povidone iodine 10%. Metode: Penelitian laboratoris yang dilakukan dengan post test only design dengan rancangan acak lengkap. Sampel penelitian adalah kultur Streptococcus viridans yang diambil melalui swab dari hapusan ulser pada pasien yang menderita stomatitis aftosa rekuren, kemudian dilakukan replikasi dengan rumus Federer. Hasil: Zona hambat ekstrak daun sirih 35% lebih besar daripada zona hambat povidone iodine 10%. Kesimpulan: Streptococcus viridans lebih sensitif terhadap ekstrak daun sirih 35%. Ekstrak daun sirih 35% memiliki efek daya antibakteri yang lebih tinggi jika dibandingkan dengan povidone iodine 10%.